2003
DOI: 10.1021/jp027785a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Colloidal Nanoparticles of Mixed Metal Oxides Containing Platinum, Ruthenium, Osmium, and Iridium and Their Use as Electrocatalysts

Abstract: The hydrolysis of H 2 PtCl 6 , RuCl 3 , OsCl 3 , and H 2 IrCl 6 under basic conditions in the presence of a watersoluble betaine stabilizer affords aqueous colloidal solutions of the mixed metal oxide PtRuOsIrO x displaying a particle size of 1.3-1.6 nm. The ratio of the four metals can be adjusted by choosing the appropriate relative amounts of metal salts. Characterization was accomplished by TEM, XPS, and XRD. Immobilization of the reduced form on high surface conducting carbon leads to materials which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Consequently, the development of CO tolerant catalysts is of vital importance in fuel cell research. Various binary and ternary Pt catalyst systems [1][2][3][4][5][6][7] have been tested recently, which show improved activity for the hydrogen oxidation reaction in the presence of CO. In particular, for the binary Pt-Ru system, an enhanced activity has been observed in reformate operation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development of CO tolerant catalysts is of vital importance in fuel cell research. Various binary and ternary Pt catalyst systems [1][2][3][4][5][6][7] have been tested recently, which show improved activity for the hydrogen oxidation reaction in the presence of CO. In particular, for the binary Pt-Ru system, an enhanced activity has been observed in reformate operation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Iridium nanoparticles, which are usually found in the form of iridium oxide, have been synthesized in a variety of ways, either as nanorods [200], as particles using solgels [201], or as colloidal suspensions containing mixed metal oxides [202]. Although several iridium structures have been prepared, their electroanalytical applications to date have primarily been in biosensors, due to their ability to catalytically oxidize and reduce hydrogen peroxide [203][204][205][206].…”
Section: Nanoparticles Of Other Metallic Speciesmentioning
confidence: 99%
“…In a follow -up study the scope and limitation of the method was defi ned [54,56] . We were particularly interested in fabricating colloidal mixed -metal oxides containing more than two metals.…”
Section: Preparation and Application Of Aqueous Colloids Of Metal Oximentioning
confidence: 99%
“…Of special interest was the work of Smotkin and Mallouk, who had shown that quaternary alloys composed of Pt, Ru, Os and Ir in the zerovalent form, prepared by other means, are highly active electrocatalysts for potential use in fuel cells [57] . Therefore, we tested our method in the preparation of a mixed metal oxide containing these four metals [56] . The hydrolysis of an aqueous mixture of H 2 PtCl 6 , RuCl 3 , OsCl 3 and H 2 IrCl 6 under basic conditions in the presence of the stabilizing surfactant 11 afforded aqueous colloidal solutions of the mixed metal oxide PtRuOsIrO x displaying a particle size of 1.3 -1.6 nm [56] .…”
Section: Preparation and Application Of Aqueous Colloids Of Metal Oximentioning
confidence: 99%